Ulcerative Colitis-induced Hematotoxicity in Mice and its Amelioration with Visnagin - V. Sravathi (The Indian Veterinary Journal, 2026)
Ulcerative Colitis (UC) is the most challenging disease in humans and animals. The present study was done to explore the potential effect of Visnagin against Dextran Sodium Sulphate (DSS) induced UC in mice, and its potential mechanism. Visnagin, a natural compound, has a range of antioxidant and anti-inflammatory effects. The mice were euthanized on the 32nd day of the experimental period, and the haematological parameters were assessed to evaluate the efficacy of the treatment. The results indicated significant improvements in the haematological parameters, suggesting that visnagin can effectively mitigate the haematological impacts of DSS-induced ulcerative colitis in mice.